Ritualization of Space and Body in Mithila Folk Arts (SIRJANĀ – A Journal Of Arts and Art Education, 2022)
This paper revisits the process of formation and ritualistic differentiation of the space of Kohbar and Aripana patterns traditionally painted on the mud walls of honeymoon chamber and the yards for pujas respectively. Kohbar and Aripana are the most celebrated folk art performances in the Mithila region of Nepal (and also in the Madhuvani District of Northern India). Kohbars are the ritualistic invocation through painted diagrams of kamala daha (seven-lotus pond motif) and several symbols of fertility and auspiciousness that are supposed to invite conjugal happiness and fertility power especially for newly married couple. Kohbars are often associated with Tantrism and procreative intercourse of opposite sex. Similarly, Aripanas are intricately designed decorative patterns performed on the sacred floor or yards especially during pujas and other auspicious occasions. The study of ritualization of space is relevant and important while studying folk art forms like Kohbar, Aripana, Ashtimki, etc. because ordinary spaces like yards, walls and floors are given special significance during such performances. These spots become sacred spaces for drawing some divine patterns and installing paraphernalia for specials rituals or pujas. The study basically incorporates Catherine Bell’s ideas on ‘Ritualization of Spaces’ and ‘Improvisation of Rituals’. The method of the study is based on the close observation of selected Kohbar and Aripana paintings as cultural texts. The critical analysis of the contents and performative details is expected to derive some cogent conclusion. This study attempts to pave the way for further studies on a number of similar folk art forms.